Internal bank fraud as a category of operational risk - Wiszniowski, Edward (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
Internal bank fraud is classified as one of the seven categories of operational risk. Even though the scale of these phenomena is marginal and their frequency incidental, internal frauds cannot be underestimated because if they emerge as an extreme event, they may cause an economic shock resulting in far-reaching financial consequences. Because of the short period of time since the implementation of the Capital Requirements Directive, Polish banks measure operational risk using simplified methods. This does not simplify or favour the disclosure of detailed information on operational risk incurred, including the disclosure of losses caused by internal fraud. The aim of this publication is to place the risk of internal fraud within the operational risk and to indicate the potential consequences of its threat. Accompanying illustrations based on examples explain mechanisms of the unlawful actions
Argumenta Oeconomica, 2011, Nr 2 (27), s. 137-172
Keywords: bank crime; internal fraud; operational risk; creative accounting